PROBABILITY MODEL FOR CARBONIZATION OF REINFORCED CONCRETE STRUCTURES - S. N. Leonovich; O. Yu. Cherniakevich (Наука и техника)
The paper describes a methodology for calculation of concrete carbonization in respect of reinforced concrete structures used under conditions of the Republic of Belarus. The equation of concrete carbonization rate is presented in the probabilistic form. Such approach makes it possible to predict the service life as new structures at the design stage so the service life of the applied structures.